2022
DOI: 10.1007/s10530-022-02787-6
|View full text |Cite
|
Sign up to set email alerts
|

The influence of native populations’ genetic history on the reconstruction of invasion routes: the case of a highly invasive aquatic species

Abstract: Brazier Thomas and Cherif Emira should be considered joint first authors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 123 publications
(152 reference statements)
0
9
0
Order By: Relevance
“…Effective population size was higher in topmouth gudgeon than in three‐spined stickleback, but lower than in stone loach. Large effective population sizes have previously been observed in topmouth gudgeon in Western Europe (Brazier et al, 2022 ). These observations suggest high gene flow between populations of topmouth gudgeon with minor effects of dispersal distance and spatial barriers on the connectivity among populations.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Effective population size was higher in topmouth gudgeon than in three‐spined stickleback, but lower than in stone loach. Large effective population sizes have previously been observed in topmouth gudgeon in Western Europe (Brazier et al, 2022 ). These observations suggest high gene flow between populations of topmouth gudgeon with minor effects of dispersal distance and spatial barriers on the connectivity among populations.…”
Section: Discussionmentioning
confidence: 67%
“…It is generally hypothesized that invasive species are genetically less diverse due to a succession of genetic bottlenecks associated with founder effects (Allendorf & Lundquist, 2003 ; Hardouin et al, 2018 ). Yet, multiple studies report higher genetic diversity in the invasive range of topmouth gudgeon compared to its native range (Baltazar‐Soares et al, 2020 ; Brazier et al, 2022 ; Simon et al, 2011 , 2014 ). The most recent analysis of the global population genetics of topmouth gudgeon (Brazier et al, 2022 ) indicates that the invasive populations found in Europe descend from native admixed population, thus potentially explaining the elevated heterozygosity, which might also increase these populations' fitness by heterosis (Keller et al, 2014 ; Roman & Darling, 2007 ; Rosenthal et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Published data indicate ancient host-parasite co-evolution with multiple introduction events occurring across Europe from admixed host population sources of P. parva [20,21]. Furthermore, S. destruens is considered as a generalist parasite with a wide host range [12,22] and high tolerance to temperature variations (from the mountainous Tcheremoch River in Ukraine to the desert wadi of Felrhir in Algeria) and several reports indicate the global spread of its healthy carrier host P. parva.…”
Section: Introductionmentioning
confidence: 99%
“…These geographic pathways followed by organisms from their source to their introduction site can provide critical information to limit propagule pressure and prevent successful establishment [ 8 ]. Important information regarding movement pathways and invasion routes may be gained by comparing the genetic makeup of an invader with the spatial genetic structure of the species in other distribution areas [ 9 12 ].…”
Section: Introductionmentioning
confidence: 99%